2013
DOI: 10.1055/s-0032-1330840
|View full text |Cite
|
Sign up to set email alerts
|

Cosmetic Tattooing of Free Flaps following Head and Neck Reconstruction

Abstract: Free flap reconstruction of the head and neck is a widespread procedure. The aesthetic outcome is frequently compromised by color mismatch between the donor site skin and the complex pigmentation of the face. Various surgical procedures have been described to improve the appearance of external skin paddles. Medical tattooing is commonly used for nipple pigmentation in breast reconstruction and cosmetic procedures such as permanent makeup. This article describes the technique and its application to head and nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Especially in the case of skin grafting or flap surgery, the wound is given sufficient time to heal before dermatography to ensure adequate perfusion and healing. 17 The results of the present study show that dermatography is a valuable adjuvant treatment option. The scores on the VAS pertaining to the appearance of the scar or skin graft improved after treatment by 4 points on a 10-point scale.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Especially in the case of skin grafting or flap surgery, the wound is given sufficient time to heal before dermatography to ensure adequate perfusion and healing. 17 The results of the present study show that dermatography is a valuable adjuvant treatment option. The scores on the VAS pertaining to the appearance of the scar or skin graft improved after treatment by 4 points on a 10-point scale.…”
Section: Discussionsupporting
confidence: 50%
“…25 Instead of traditional ink that is used in decorative tattooing, inorganic metallic salts (eg, iron oxide dyes) and organic molecules (eg, tartrazine) are used as coloring agents in dermatography because of their structure that gives a more precise result. 17 The association be-tween tattooing and skin cancer is most likely multifactorial, including trauma induced by the procedure, a lifetime inflammatory reaction in an attempt to degrade all foreign material, and the ink content used. 25 However, a review by Kluger et al 25 concluded that the number of skin cancers arising in tattoos is low and that any association thus far should be considered coincidental.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include, but are not limited to, osteotomies of otherwise straight bones used in jaw reconstructions (Fig. ) to more curved contours, cosmetic tattooing to improve colour and facial prosthetics. Aesthetic considerations although very important, are of secondary concern when compared to function.…”
Section: Discussionmentioning
confidence: 99%